HIV infection, antiretroviral therapy and the haemostasis of pregnancy - Schapkaitz, Elise (University of the Witwatersrand, Johannesburg, 2023)
The human immunodeficiency virus (HIV) epidemic affects an estimated 30% of pregnant women living in South Africa. Increasing evidence suggests that women living with HIV are at a heightened risk for venous thrombo-embolism (VTE), which is a significant contributor to maternal mortality. In addition to a higher prevalence of obstetric and venous risk factors, this increased risk of VTE has been attributed to the effects of HIV and/or its treatment. HIV is characterized by immune activation and inflammation, which promote endothelial dysfunction and activation of coagulation. This is more pronounced with untreated HIV, yet this pro-inflammatory and pro-thrombotic balance may persist with long-term suppressive antiretroviral therapy (ART). However, the extent to which ongoing inflammation disrupts maternal haemostasis and predisposes pregnant women living with HIV to its prothrombotic consequences, is currently unknown. The aims of the work presented in this thesis in women living with HIV with access to ART were firstly to identify antepartum and postpartum risk factors for VTE; secondly to assess procoagulant changes in maternal haemostasis; and thirdly to determine risks of thrombosis and bleeding associated with thromboprophylaxis for VTE prevention. An epidemiological case-control study was performed in 128 cases with pregnancy related VTE and 640 matched controls. This study found at least a two-fold increased risk for VTE among pregnant and postpartum women living with HIV. In addition, antepartum risk factors, that may explain the disproportion of VTE risk in HIV, included medical co-morbidities and chronic hypertension, while postpartum risk factors included a personal history of VTE, medical co-morbidities, systemic infection, prolonged hospital admission and postpartum haemorrhage. Opportunistic infections, ART and the degree of immunosuppression were not associated with VTE risk. A sub-study followed and investigated antiphospholipid antibodies (aPL) in 215 women with thrombosis and/or obstetric complications. In this study, 15 (13.2%) of the women with HIV were positive at baseline for one of the five criteria aPL. The prevalence of aPL was not significantly increased among women with HIV, as compared to HIV negative women. Furthermore, the aPL profiles were not significantly different between the two groups. Lupus anticoagulant (LAC) positivity, on a single occasion, was associated with thrombosis (p < 0.003). Subsequently two prospective cross-sectional studies were conducted which assessed endothelial activation as well as fibrinolysis, coagulation and platelet activation in pregnant women with HIV, in each trimester. The studies included three groups: HIV negative, HIV with virological suppression (< 50 copies/mL) and HIV with viral load (VL) of >50 copies/mL. Endothelial activation was evaluated by measuring von Willebrand factor (VWF) antigen, VWF propeptide, multimer patterns and ADAMTS-13 antigen, activity, and antibody levels. The results showed an increase in the ratio of VWF propeptide to VWF antigen in the first, second and third trimester, in the HIV virologically suppressed group (1.7 ± 0.7, 1.7 ± 0.4, 1.6 ± 0.5) and the HIV group with VL > 50 copies/mL (1.9 ± 0.9, 1.7 ± 0.9, 1.6 ± 1.1) compared to the HIV negative group (1.4 ± 0.6, 1.3 ± 0.4, 1.2 ± 0.3, p < 0.05). Virological suppression was not associated with a significant reduction in this ratio, in each trimester. In addition, increased high molecular weight multimers were observed in the HIV groups, despite only a mild reduction in ADAMTS-13 activity compared to the HIV negative group (p < 0.001). Thereafter, fibrinolytic activity was evaluated by measuring d-dimer and plasminogen activator inhibitor-1 (PAI-1). Coagulation activity was determined by measuring thrombin-antithrombin (TAT) complex concentrations, and platelet factor-4 and platelet indices, namely mean platelet volume (MPV) and platelet distribution width as a measure of platelet activation. The results showed increased log d-dimer levels in the first, second and third trimester, in the HIV virologically suppressed group (-1.2 ± 0.5, -0.9 ± 0.4, -0.5 ± 0.3) and the HIV group with VL > 50 copies/mL (- 1.1 ± 0.4, -0.7 ± 0.4, -0.5 ± 0.5) compared to the HIV negative group (-1.4 ± 0.2, -1.1 ± 0.3, -0.8 ± 0.3, p < 0.05). Additionally, log PAI-1 levels were increased in the first, second, and third trimester, in the HIV virologically suppressed group (1.0 ± 0.4, 1.3 ± 0.4, 1.5 ± 0.4) and the HIV with VL > 50 copies/mL (0.8 ± 0.5, 1.2 ± 0.4, 1.5 ± 0.3) compared to the HIV negative group (0.4 ± 0.5, 0.8 ± 0.3, 1.3 ± 0.3, p < 0.05). Virological suppression was not associated with a significant reduction in first and third trimester d-dimer and PAI-1 levels. Thrombin-antithrombin complex levels were not increased, in the HIV virologically suppressed group as compared to the HIV negative group, beyond the first trimester. With regard to platelet parameters, only log MPV measured in the third trimester was decreased in in the HIV virologically suppressed group (2.3 ± 0.1) and the HIV group with VL > 50 copies/mL (2.3 ± 0.1) compared to the HIV negative group (2.5 ± 0.2) (p < 0.001). The last study was a longitudinal study of 129 pregnant women at intermediate or high risk of VTE, who received thromboprophylaxis. Venous thrombo-embolism occurred antepartum in 1.4%, 95% confidence interval (CI) 0.04-7.7 of intermediate and 3.4%, 95% CI 0.4-11.7 of high risk pregnancies. Major, clinically relevant non-major and minor bleeding events occurred in 7.1%, 95% CI 2.4-15.9 of intermediate and 8.5%, 95% CI 2.8-18.7 of high risk pregnancies. Owing to the small number of events, this study could not assess for HIV as a predictor of thrombosis and bleeding. Thus, in conclusion, the findings described in the studies in this thesis contribute to our knowledge in pregnant women living with HIV in the following ways. Firstly, HIV emerged as a significant antepartum and postpartum risk factor for VTE. Traditional obstetric and venous risk factors were also linked to the risk of thrombosis and could be useful for identifying women with HIV, who may benefit from postpartum and/or antepartum thromboprophylaxis. Secondly, this thesis identified heightened markers of endothelial activation and impaired fibrinolysis. Markers such as the ratio of VWF propeptide to VWF antigen, d-dimer and PAI-1 may provide a biological mechanism for the increased risk of pregnancy-related VTE in in HIV. Finally, this thesis provided rates of thrombosis and bleeding in women who received thromboprophylaxis in pregnancy and the postpartum period which can be used to advise women with HIV of the associated risks.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: HIV; ART; Pregnancy; Coagulation; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education